α3β1 integrin–controlled Smad7 regulates reepithelialization during wound healing in mice - Reynolds, Louise E. (American Society for Clinical Investigation, 2008)
Effective reepithelialization after injury is essential for correct wound healing. The upregulation of keratinocyte α3β1 integrin during reepithelialization suggests that this adhesion molecule is involved in wound healing; however, its precise role in this process is unknown. We have shown here that retarded reepithelialization in Itga3(–/–) mouse skin wounds is due predominantly to repressed TGF-β1–mediated responses. Specifically, expression of the inhibitor of TGF-β1–signaling Smad7 was elevated in Itga3(–/–) keratinocytes. Indeed, in vivo blockade of Smad7 increased the rate of reepithelialization in Itga3(–/–) and WT wounds to similar levels. Our data therefore indicate that the function of α3β1 integrin as a mediator of keratinocyte migration is not essential for reepithelialization but suggest instead that α3β1 integrin has a major new in vivo role as an inhibitor of Smad7 during wound healing. Moreover, our study may identify a previously undocumented function for Smad7 as a regulator of reepithelialization in vivo and implicates Smad7 as a potential novel target for the treatment of cutaneous wounds.